Caracterização de árvores, frutos e diversidade genética em populações naturais de mangaba - da Silva, Ana Veruska Cruz; Amorim, Julie Anne Espíndola [UNESP]; da Vitória, Marina Ferreira; da Silva Ledo, Ana; Rabbani, Allivia Rouse Carregosa (FapUNIFESP (SciELO), 2017)
The state of Sergipe is the largest mangaba producer, which is a fruit native to Brazil, and has cultural, social and economic importance in its area of occurrence. It is an endangered species due to human actions, and despite its economic potential, there are still no commercial plantations. The study was carried out in order to characterize trees, fruits and the genetic diversity of natural populations of mangaba in Sergipe, Brazil. Fruits from Abaís Beach/Estância (AB) presented, on average, twice the vitamin C content (414.81 mg of vit. C/100g), when compared with the others. The use of ISSR primers was efficient in estimating the genetic similarity of populations. The primers clustered the populations of mangaba according to their origin, which indicates the genetic diversity of mangaba and their isolation. The results can be used to guide the selection of individuals in situ and ex situ conservation actions of these genetic resources.
Characterization of trees, fruits and genetic diversity in natural populations of mangaba
Keywords: Hancornia speciosa gomes; Molecular markers; Postharvest; Variability